2004
DOI: 10.3354/meps284269
|View full text |Cite
|
Sign up to set email alerts
|

Long-term increases in prevalence of North Sea fishes having southern biogeographic affinities

Abstract: Observations made in the scientific and popular literature suggest that the characteristics of both marine and terrestrial ecosystems are changing rapidly due to increasing global air and sea temperatures. Here, we examine the hypothesis that fish species with more 'southern' distributions are increasing in the northern North Sea over time. In order to do this, 2 important databases on fish abundance collected by trawl on research cruises are interrogated. When combined, the databases cover both the entire Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
114
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(126 citation statements)
references
References 29 publications
11
114
1
Order By: Relevance
“…Since demersal trawls are relatively unselective, trawl surveys can provide information not only on target species, but also on potentially key members of benthic communities. In this way, lengthy time series of trawl surveys are rare but are clearly essential for assessing the impact of natural and anthropogenic changes in benthic communities (Beare et al, 2004(Beare et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Since demersal trawls are relatively unselective, trawl surveys can provide information not only on target species, but also on potentially key members of benthic communities. In this way, lengthy time series of trawl surveys are rare but are clearly essential for assessing the impact of natural and anthropogenic changes in benthic communities (Beare et al, 2004(Beare et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…(2015) 416, 27 Temperature is one of the most important abiotic factors controlling the dynamics of larval assemblages of freshwater and marine fish species (Houde and Zastrow, 1993;Jakobsen et al, 2009). Many studies have linked temperature changes to distributional changes of fish stocks, mainly in marine ecosystems (Beare et al, 2004;Alheit et al, 2005;Perry et al, 2005;Pörtner and Peck, 2010) but also in freshwater ecosystems (Hari et al, 2006;Lassalle et al, 2008;Almodovar et al, 2012). However, only few studies have demonstrated temperature sensitivity of individual species based on physiological principles (Pörtner and Peck, 2010).…”
mentioning
confidence: 99%
“…Distribution shifts in a sense of natural range expansion of, for example, southern species into the German EEZ were also found in the last decades. Recently, the angular crab G. rhomboides extended its distribution from the eastern Atlantic to the southern North Sea (Neumann et al 2010) and also southern fish species such as the tub gurnard Trigla lucerna, the red mullet Mullus surmuletus and the pilchard Sardina pilchardus were now regularly found in the German Bight (Ehrich and Stransky 2001;Beare et al 2004;Ehrich et al 2007). In contrast, Kröncke et al (2011) found no indications for range expansions of non-native benthic infauna species by a comparison of infauna communities between 1986 and 2000 on a North Sea wide scale.…”
Section: Discussionmentioning
confidence: 99%